2019
DOI: 10.1521/pedi_2019_33_424
|View full text |Cite
|
Sign up to set email alerts
|

Personality Pathology Profiles as Moderators of the Growing Pro-Social Program: Outcomes on Cognitive, Emotion, and Behavior Regulation in Male Prison Inmates

Abstract: This study consisted of secondary data analysis of information collected from inmates who had participated in an earlier independent randomized controlled trial testing the effects of the Growing Pro-Social (GPS) program. The current study assessed personality disorders as moderators of the GPS effects in cognitive malfunctioning, emotion regulation strategies, and prison misconduct in male prison inmates. Participants were 254 inmates randomly assigned to either the GPS (n = 121) or the control group (n = 133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
3
0
3
Order By: Relevance
“…The positive effects of a rehabilitation program over recidivism rates are usually presented as a major requirement for the selection of effective intervention practices (e.g., McGuire, 2013). However, a recent trend in research (e.g., Antonio & Crosset, 2017;Brazão et al, 2017Brazão et al, , 2018aBrazão et al, , 2018bBrazão et al, , 2019Skeem et al, 2009) has begun to identify and to assess other relevant variables as treatment outcome measures, namely cognitive and emotional correlates of antisocial behavior. The current study added to this new wave of research and proposed to test the effects of a cognitive-behavioral structured group intervention program in cognitive and emotional correlates of antisocial behavior.…”
Section: Table 5 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effects of a rehabilitation program over recidivism rates are usually presented as a major requirement for the selection of effective intervention practices (e.g., McGuire, 2013). However, a recent trend in research (e.g., Antonio & Crosset, 2017;Brazão et al, 2017Brazão et al, , 2018aBrazão et al, , 2018bBrazão et al, , 2019Skeem et al, 2009) has begun to identify and to assess other relevant variables as treatment outcome measures, namely cognitive and emotional correlates of antisocial behavior. The current study added to this new wave of research and proposed to test the effects of a cognitive-behavioral structured group intervention program in cognitive and emotional correlates of antisocial behavior.…”
Section: Table 5 (Continued)mentioning
confidence: 99%
“…Nevertheless, so far, the efficacy of GPS was tested exclusively with adult samples. A randomized controlled trial testing the GPS's effects over time in a sample of male prison inmates was accomplished (Brazão et al, 2017(Brazão et al, , 2018a(Brazão et al, , 2018b(Brazão et al, , 2019. Results showed that the GPS program had positive effects on the offenders' cognitive functioning, by reducing cognitive distortions and the prominence of EMSs.…”
Section: Introductionmentioning
confidence: 99%
“…A empatia tem a função de diminuir a probabilidade do sujeito exibir comportamentos inadequados, em particular, agressivos ou anti-sociais (Covell & Scalora, 2002;Jolliffe & Farrington, 2004). O défice empático pode tornar o sujeito vulnerável, facilitanto actos de natureza agressiva (Brasão et al, 2019;Fonseca et al, 2019;Hunter & Longo, 2004;Jolliffe & Farrington, 2004). Os défices empáticos nem sempre são um traço estável do indivíduo, podendo ser específicos de uma determinada situação ou pessoa (Hunter et al, 2007;Santos & Mesquita, 2019;Websler et al, 2005).…”
Section: Introductionunclassified
“…Nos violadores os sinais de sofrimento da vítima não inibem a excitação sexual, porque apresentam uma falha ao nível do défice empático específico para com a vítima. Os défices de empatia correlacionam com défice de competências sociais, baixa auto-estima, distorções cognitivas e défice ao nível do controlo dos impulsos (Blake & Gannon, 2008;Brasão et al, 2019;Covell & Scalora, 2002;Varker et al, 2008). Os agressores sexuais tendem a usar determinadas estratégias, dependendo do grau de conhecimento prévio com a vítima, da idade desta e das características que evidencia (Costa, 2002;Fávero, 2003;Furniss, 1993;Hunter, 1990;Sanderson, 2005;Singer et al, 1992).…”
Section: Introductionunclassified
“…Drug abuse leads to health deterioration negative social consequences, the poor quality of life (Karim et al, 2019;Mohamad, Karim, et al, 2017); psychological problems; related with psychiatric disorders, infectious diseases, and pain conditions (Zibbell et al, 2015); and, exhibiting Anti-Social Personality Disorder (ASPD) (Smith et al, 2017). A study by Brazão et al, (2019) found that ASPD is the most common diagnosis among inmates. They also might tend to experience stress and suicidal idealization (Jahn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%